Controle e repressão em uma sociedade de classes: estudo da institucionalização e do processo educativo de dois abrigos infantis em Bragança Paulista - Silva, Mônica Nardy Marzagão (2009)
This work discusses the institutionalization of children and education of ISE - Institute of Social and Educational and Sama - Food Medical Service, both in Bragança Paulista, São Paulo State, from its foundation until the present day. The establishments had and are intended to house abandoned children (read poor), symbolizing a political action intended to mix life and rules of conduct for them, based health-medical discourse, in its way prophylactic in nature extremely ideological. The theoretical assumption that the discussion Embase were the work of Goldmann and Foucault, with its discursive articulation based on documentary sources and of those involved in the historical process of incorporation of each institution examined. The intention motivating the research was to recognize what was behind the two institutions, namely the political relationship between the practice of sheltering and ideals of the Brazilian state, in its authoritarian aspects. Waste derived from the logic of capitalist rationalization updated, corrective and educational practices in both institutions, had to be exclusionary and disciplinary functions, in response to the demands of the dominant elites in that historical moment of the Brazilian reality